Expansion in the latitudinal distribution of Rhipicephalus sanguineus sensu stricto (Acari: Ixodidae) to southern Chile - Oyarzún Ruiz, Pablo (2021)
Rhipicephalus sanguineus is a species complex with a challenging diagnosis. There are two main lineages: a temperate lineage—now recognized as R. sanguineus sensu stricto (s.s.)—and a tropical lineage. In the Americas, several studies examined the distribution of both lineages. Meanwhile, in Chile, the distribution of the tropical lineage was reported from 18° to 22° S and R. sanguineus s.s. from 20° to 33° S; the morphological diagnosis located R. sanguineus in south-central Chile. In this study, we assessed the morphological and genetic identity of ticks collected from 47 dogs in southern Chile. Six dogs (12.8%) were parasitized by ticks that were morphologically and genetically assigned to R. sanguineus s.s. This finding would represent the southernmost record of this species in the country, located at over 308 km further south than the previous record, suggesting a latitudinal expansion of its distribution. Experimental studies are further required to understand how this tick survives extreme weather conditions when compared to other R. sanguineus s.s. from lesser latitudes.